2005
DOI: 10.1095/biolreprod.104.038919
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Motherhood Decreases Life Expectancy of Mouse Offspring1

Abstract: This study analyzes the long-term effects of delayed motherhood on reproductive fitness and life expectancy of offspring in the mouse. Hybrid (C57BL/6JIco x CBA/JIco) first-generation (F1) females, either at the age of 10 or 51 wk, were individually housed with a randomly selected 12- to 14-wk-old hybrid male following a breeding pen system until females reached the end of their reproductive life. Reproductive fitness of second-generation (F2) females was tested from the age of 25 wk until the end of their rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 33 publications
7
39
1
Order By: Relevance
“…The finding of a beneficial effect of young maternal age on offspring survival to age 100 in humans is similarly also reported for laboratory animals (Carnes et al 2012; Tarin et al 2005), and hence may have a biological explanation. There is empirical evidence that the quality of female eggs in humans rapidly declines with age (Bickel 2005; Pellestor et al 2005; Comings and MacMurray 2001; Comings and MacMurray 2006) and that this deterioration starts rather early—before age 30 (Heffner 2004).…”
Section: Centenarians Compared To Their Shorter-lived Siblings: Thesupporting
confidence: 69%
“…The finding of a beneficial effect of young maternal age on offspring survival to age 100 in humans is similarly also reported for laboratory animals (Carnes et al 2012; Tarin et al 2005), and hence may have a biological explanation. There is empirical evidence that the quality of female eggs in humans rapidly declines with age (Bickel 2005; Pellestor et al 2005; Comings and MacMurray 2001; Comings and MacMurray 2006) and that this deterioration starts rather early—before age 30 (Heffner 2004).…”
Section: Centenarians Compared To Their Shorter-lived Siblings: Thesupporting
confidence: 69%
“…Experiments on laboratory mice found that the offspring born to younger mothers live longer (Tarin et al, 2005). This study also demonstrated that the largest effect is observed at later life.…”
Section: Resultsmentioning
confidence: 99%
“…Data analyzed in this study were extracted from a database generated in two previous studies designed to ascertain the long-term effects of maternal [14] and paternal [15] aging on offspring’s reproductive fitness and longevity. All the animal experiments performed in these studies were conducted in accordance with the National Research Council’s publication Guide for the Care and Use of Laboratory Animals [16].…”
Section: Methodsmentioning
confidence: 99%